Urolithin A targets the AKT/WNK1 axis to induce autophagy and exert anti-tumor effects in cholangiocarcinoma - Sahashi, Hidenori; Kato, Akihisa; Yoshida, Michihiro; Hayashi, Kazuki; Naitoh, Itaru; Hori, Yasuki; Natsume, Makoto; Jinno, Naruomi; Kachi, Kenta; Asano, Go; Toyohara, Tadashi; Kito, Yusuke; et al. (Frontiers in Oncology, 2022)
Urolithin A (UA; 3,8-dihydroxybenzo[c]chromen-6-one), a metabolite generated by intestinal bacteria during the biotransformation of ellagitannins, has gained considerable attention in treating several cancers. Cholangiocarcinoma (CCA) remains one of the most lethal cancers; it grows in a special environment constantly exposed to both blood and bile. Since UA is known to undergo enterohepatic recirculation, we hypothesized that UA might have significant antitumor effects in CCA. Here, we investigated the therapeutic potential of UA in CCA and aimed to elucidate its mechanisms, including autophagy. UA treatment inhibited cell proliferation and induced G2/M phase cell cycle arrest in CCA cells. UA also suppressed cell migration and invasion, but did not cause apoptosis. Furthermore, Western blotting and immunocytochemistry demonstrated increased LC3-II accumulation, while electron microscopy demonstrated induced autophagosomes after UA treatment, suggesting that UA upregulated autophagy in CCA cells. In xenograft mice treated with UA, tumor growth was inhibited with increased LC3-II levels. On the other hand, phospho-kinase array demonstrated downregulation of the AKT/WNK1 pathway. LC3-II expression was elevated in WNK1 knocked down cells, indicating that WNK1 is the key signal for regulating autophagy. Thus, UA exerted antitumor effects by suppressing the AKT/WNK1 signaling pathway and inducing autophagy. In conclusion, UA, a natural, well-tolerated compound, may be a promising therapeutic candidate for advanced CCA.